Central Line-Associated Blood Stream Infections and Non–Central Line-Associated Blood Stream Infections Surveillance in Canadian Tertiary Care Neonatal Intensive Care Units - Zipursky, Amy R.; Yoon, Eugene W.; Emberley, Julie; Bertelle, Valerie; Kanungo, Jaideep; Lee, Shoo K.; Shah, Prakesh S.; Ting, Joseph; Cieslak, Zenon; Sherlock, Rebecca; Yee, Wendy; Toye, Jennifer; et al. (The Journal of pediatrics, 2019)
To determine if the reported reduction in hospital-acquired infections is due to reduced central line-associated blood stream infections (CLABSI) or non-CLABSIs. A retrospective cohort study design was used to describe the change in organism pattern and incidence of hospital-acquired infections (CLABSIs and non-CLABSIs) in neonates <33 weeks of gestation admitted to tertiary neonatal intensive care units in the Canadian Neonatal Network between January 1, 2010, and December 31, 2016. Hospital-acquired infection was diagnosed when a pathogenic organism was isolated from blood or cerebrospinal fluid in a neonate with suspected sepsis. CLABSI was diagnosed when a central venous catheter was present at the time or removed in the 2 days before a hospital-acquired infection diagnosis. Cochran-Armitage and Mann-Kendall trend tests and linear regression models were used for statistical analyses. Of 28 144 eligible neonates from 30 Canadian Neonatal Network neonatal intensive care units, 3306 (11.7%) developed hospital-acquired infections. There was a significant decrease in the rate of hospital-acquired infections (14.2% in 2010 and 9.2% in 2016; P < .01), and the rate of both CLABSIs and non-CLABSIs (P < .01) over the study period concomitant with a significant decrease in the duration of central line use (P = .01). The rates of meningitis also decreased during the study period (1.2% in 2010 and 0.9% in 2016; P < .01). Infections owing to gram-positive cocci significantly decreased, but infections owing to gram-negative organisms remained unchanged. Although there was a significant decrease in CLABSIs and non-CLABSIs, hospital-acquired infections in preterm neonates remained high. Infections owing to gram-negative organisms remained unchanged and are a target for future preventative efforts.